EDUCATION ABOUT SUSTAINABLE TOURISM IN THE CONTEXT OF CLIMATE CHANGE - Tri, Nguyen Minh (Language and Literature Faculty, Universitas Sains Al-Qur'an (UNSIQ) Jawa Tengah di Wonosobo, 2024)
In the face of accelerating climate change, the tourism industry must adopt sustainable practices to mitigate its environmental impact and promote long-term resilience. This paper explores the critical role of education in fostering sustainable tourism within the context of climate change. It examines the current educational frameworks and their efficacy in imparting knowledge about sustainable tourism practices. The research highlights the importance of integrating climate change awareness into tourism education to create a well-informed workforce capable of implementing and advocating sustainable strategies. The findings suggest that comprehensive education on sustainable tourism is aligned with climate change mitigation and adaptation strategies. The paper concludes with recommendations for policymakers, educators, industry leaders, and the local community to collaborate in developing robust educational initiatives that promote sustainable tourism practices in the era of climate change.